Myosteatosis is associated with poor physical fitness in patients undergoing hepatopancreatobiliary surgery. Issue 4 (21st May 2019) - West, Malcolm A.; van Dijk, David P.J.; Gleadowe, Fredrick; Reeves, Thomas; Primrose, John N.; Abu Hilal, Mohammed; Edwards, Mark R.; Jack, Sandy; Rensen, Sander S.S.; Grocott, Michael P.W.; Levett, Denny Z.H.; Olde Damink, Steven W.M.
Abstract: Background: Body composition assessment, measured using single‐slice computed tomography (CT) image at L3 level, and aerobic physical fitness, objectively measured using cardiopulmonary exercise testing (CPET), are each independently used for perioperative risk assessment. Sarcopenia (i.e. low skeletal muscle mass), myosteatosis [i.e. low skeletal muscle radiation attenuation (SM‐RA)], and impaired objectively measured aerobic fitness (reduced oxygen uptake) have been associated with poor post‐operative outcomes and survival in various cancer types. However, the association between CT body composition and physical fitness has not been explored. In this study, we assessed the association of CT body composition with selected CPET variables in patients undergoing hepatobiliary and pancreatic surgery. Methods: A pragmatic prospective cohort of 123 patients undergoing hepatobiliary and pancreatic surgery were recruited. All patients underwent preoperative CPET. Preoperative CT scans were analysed using a single‐slice CT image at L3 level to assess skeletal muscle mass, adipose tissue mass, and muscle radiation attenuation. Multivariate linear regression was used to test the association between CPET variables and body composition. Main outcomes were oxygen uptake at anaerobic threshold ( V ̇ O2 at AT), oxygen uptake at peak exercise ( V ̇ O2 peak), skeletal muscle mass, and SM‐RA. Results: Of 123 patients recruited [77 men (63%), median age 66.9 ± 11.7, median body mass index 27.3 ± 5.2], 113 patients had good‐quality abdominal CT scans available and were included. Of the CT body composition variables, SM‐RA had the strongest correlation with V ̇ O2 peak ( r  = 0.57, P  < 0.001) and V ̇ O2 at AT ( r  = 0.45, P  < 0.001) while skeletal muscle mass was only weakly associated with V ̇ O2 peak ( r  = 0.24, P  < 0.010). In the multivariate analysis, only SM‐RA was associated with V ̇ O2 peak ( B  = 0.25, 95% CI 0.15–0.34, P  < 0.001, R 2  = 0.42) and V ̇ O2 at AT ( B  = 0.13, 95% CI 0.06–0.18, P  < 0.001, R 2  = 0.26). Conclusions: There is a positive association between preoperative CT SM‐RA and preoperative physical fitness ( V ̇ O2 at AT and at peak). This study demonstrates that myosteatosis, and not sarcopenia, is associated with reduced aerobic physical fitness. Combining both myosteatosis and physical fitness variables may provide additive risk stratification accuracy and guide interventions during the perioperative period.